An Analysis of Shrimp Aquaculture Techniques In Secanggang District, Langkat Regency, Sumatera Utara Province - Rahmadhayani , Anisa; Nasution, Zulkifli; Purwoko, Agus (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Aquaculture is an industry that has a tremendous opportunity. Indonesia's aquaculture prospects are rising. Langkat Regency is a region in Sumatera Utara Province located in the East Coastal Region with good options for brackish water aquaculture. There are four goals in this study. This study aimed to analyze the distribution of shrimp aqua farm locations in the Secanggang District, investigate the type of shrimp aquaculture in the district, analyze the economic aspects of shrimp aquaculture in Secanggang District and study the optimal aquaculture strategy as a priority for developing coastal areas in Secanggang District. This study uses a quantitative approach to conduct a descriptive study. Three steps are applied to analyze the data: Regional distribution, economic, and analytical hierarchy. The study shows that the aqua farms in Secanggang District are located in the production area, converted forest area, wildlife nature reserve, and production forest. There are four types of Shrimp aquaculture in Secanggang District: intensive, semi-intensive, traditional, and natural/organic. The study also shows the economic analysis of costs, income, and the efficiency of R/C ratios per cycle on four types of aquaculture. This study also indicates that shrimp aquaculture using the intensive technique is the most appropriate and priority for shrimp aqua farming development in Secanggang District.